1997
DOI: 10.1161/01.cir.96.4.1165
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Hemodynamic Efficacy of Therapy Tailored to Reduce Filling Pressures in Survivors With Advanced Heart Failure

Abstract: During chronic therapy tailored to early hemodynamic response in advanced heart failure, acute vasodilator response persists, and near-normal filling pressures can be maintained in patients who survive without transplantation. Stroke volumes at low filling pressures increase further over time. Chronic hemodynamic improvement was accompanied by symptomatic improvement, but the contributions of the monitored hemodynamic approach, increased vasodilator doses, and comprehensive outpatient management have not yet b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0
6

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(109 citation statements)
references
References 40 publications
0
103
0
6
Order By: Relevance
“…They can also decrease systemic vascular resistance, decrease ventricular workload, increase stroke volume and improve cardiac output (81). Nitroglycerin is a vasodilator commonly used to relieve pulmonary congestion in patients with AHF.…”
Section: Vasodilatorsmentioning
confidence: 99%
“…They can also decrease systemic vascular resistance, decrease ventricular workload, increase stroke volume and improve cardiac output (81). Nitroglycerin is a vasodilator commonly used to relieve pulmonary congestion in patients with AHF.…”
Section: Vasodilatorsmentioning
confidence: 99%
“…This is perhaps not surprising; although SVR is increased in untreated HF, it is normal or even reduced in patients with well-treated HF such as those we studied. 30 Although small, statistically nonsignificant clinical differences (ie, cardiovascular risk profile) may have had some bearing on the vascular responsiveness to the various NPs, the degree of atherosclerotic burden in the forearm circulation is generally believed to be relatively minor. Furthermore, our study design does not allow us to differentiate if the reduced vasodilation during NP/LNMMA co-infusion compared with NP infusion is caused by blockade of basal NO or by blockade of an NO-dependent component of (A)NP-induced vasodilation.…”
Section: Study Limitationsmentioning
confidence: 99%
“…While some investigators assert that abnormal strain and strain rate in HFNEF patients is a simply a function of intrinsic diastolic dysfunction [23], others have reported a correlation between reduced systolic strain and strain rate and elevated end diastolic pressure, and have concluded that such abnormalities are probably load-dependent [24]. At discharge, higher left ventricular fi lling pressures are an accurate predictor of repeat hospitalization and increased mortality [25,26]. While the overall accuracy of E/e' for prediction of diastolic fi lling pressure remains the subject of intense debate [27,28], our results agree with fi ndings from several recent studies examining the relation between elevated E/e' at discharge and increased readmission rates [29,30].…”
Section: Discussionmentioning
confidence: 99%